The Effects of Colonialism on Indigenous Conflict Resolution Systems Among Pokot and Turkana Communities (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Colonialism impacted local cultures far beyond their infrastructure, government and geography. In addition to eroding indigenous power structures, the structural violence inflicted during colonialism left native populations with lasting self-doubt and rejection of traditional practices. Among these rejected traditions are informal processes of resolving conflict. Conflict resolution methods in different cultures often vary greatly in underlying values and perceptions. Western judicial systems reflect individualistic, highly uncertainty avoidant, low-context tendencies, while indigenous conflict resolution methods reflect collectivistic, minimally uncertainty avoidant, high-context tendencies. Research into the current state of formal courts and informal justice forums in Pokot and Turkana Counties provides case study-based evidence arguing that the transition from restorative justice (Lapai) offered by indigenous justice mechanisms to retributive justice catalyzed by colonialism has effectively weakened both the Turkana and Pokot systems of justice. Due to impacted value systems, neither the restorative, social harmony focus of traditional processes, nor the retributive, compensatory justice focus of the formal judicial system make the available forums wholly appropriate or adequate resources. This has left the two communities torn between two distinct choices, the western and indigenous approaches in conflict management. The main objective of this research was to investigate the effects of colonialism on indigenous conflict management in Pokot and Turkana counties. These were both positive and negative effects. To achieve this objective the overarching question that guided this research was; “how did colonialism affect the indigenous approaches of conflict management in Pokot and Turkana counties? The research was designed to apply qualitative research methods. Both structured and less structured interviews were conducted along the Turkana-Pokot borders. This paper proposes a hybrid model in conflict management not only for the Pokot and Turkana pastoral communities but also to other pastoral communities with similar set-ups.
Keywords: Lapai; formal; informal; indigenous; Kokwo; tree of men; restorative; punitive; retributive justice; communities; Pokot; Turkana